2015
DOI: 10.1016/j.biombioe.2015.04.023
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic carbon metabolism in a fast growing mixotrophic freshwater microalgal species Micractinium inermum

Abstract: Available online xxxKeywords: Microalgae Carbon dioxide Mixotrophic growth Synergistic Biodiesel Dissolved inorganic carbon a b s t r a c tIn recent years microalgae have attracted significant interest as a potential source of sustainable biofuel. Mixotrophic microalgae are able to simultaneously photosynthesise while assimilating and metabolising organic carbon. By combining autotrophic and heterotrophic metabolic pathways biomass productivity can be significantly increased. In this study, acetate-fed mixotro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
38
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(45 citation statements)
references
References 35 publications
5
38
0
2
Order By: Relevance
“…That Ф PSII was inhibited (as also reported by Cabrerizo et al 2018) and specific-PP stimulated by temperature was due probably to a change in coupling between electron transfer and C fixation (Moore et al 2003, Wagner et al 2006, Carrillo et al 2015. The stimulation of both types of metabolism in I. galbana appears to be related to (Halac et al 2014) and R (Smith et al 2015). However, temperature as a single factor exerted a negative effect on specific-PP of Chromulina sp., in agreement with the results reported by Princiotta et al (2016) for the chrysophyte Dinobryon sociale and by Sutton (1972) for Chromulina chionophila.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…That Ф PSII was inhibited (as also reported by Cabrerizo et al 2018) and specific-PP stimulated by temperature was due probably to a change in coupling between electron transfer and C fixation (Moore et al 2003, Wagner et al 2006, Carrillo et al 2015. The stimulation of both types of metabolism in I. galbana appears to be related to (Halac et al 2014) and R (Smith et al 2015). However, temperature as a single factor exerted a negative effect on specific-PP of Chromulina sp., in agreement with the results reported by Princiotta et al (2016) for the chrysophyte Dinobryon sociale and by Sutton (1972) for Chromulina chionophila.…”
Section: Discussionsupporting
confidence: 68%
“…) and R (Smith et al. ). However, temperature as a single factor exerted a negative effect on specific‐PP of Chromulina sp., in agreement with the results reported by Princiotta et al.…”
Section: Discussionmentioning
confidence: 99%
“…The lipid production of P. tricornutum was only different, and significantly higher, in red light autotrophic (R) or mixotrophic supplemented with glycine (R2) conditions ( Figure 1B). The latter was expected, as studies have reported an increase in biomass and lipids by multi-fold under mixotrophic conditions in different species [27,28]. Furthermore, many studies have shown a positive trend of red light with an increase in the specific growth rate and lipid production in Chlorella, Botryococcus, and Nannochloropsis [7,26,29].…”
Section: Effect Of Light Colors On Biomass and Lipid Yield In Mixotromentioning
confidence: 74%
“…The activity of both photosynthesis and respiration decreases with ageing of the microalgae culture (Emerson and Lewis, 1939;Sargent, 1940;Pratt, 1943;Kulandaivelu and Senger, 1976;Fan et al, 2014). Maximum photosynthetic activity usually occurs in the first half or middle of the exponential growth phase (Winokur, 1949;Samuelsson and Oquist, 1977;Orus et al, 1991;Yang et al, 2000;Smith et al, 2015). Our previous studies showed that under autotrophic conditions, respiration and photosynthesis intensity slow down in the middle of the C. reinhardtii culture EG (Puzanskiy et al, 2015a).…”
Section: Introductionmentioning
confidence: 96%
“…Due to the elevation of cell density and intensive microalgae metabolism, the content of C i and O 2 in the media varies. Under autotrophic conditions, the oxygen content generally increases, and the C i content decreases (Kim et al, 2013;Smith et al, 2015). Frequently, the growth of the microalgae population in culture is also accompanied by pH alteration in the media.…”
Section: Introductionmentioning
confidence: 99%